Insecticidal activity and underlying molecular mechanisms of a phytochemical plumbagin against Spodoptera frugiperda - Sun, Xiaoyu; Li, Wenxuan; Yang, Shuang; Ni, Xueqi; Han, Shengjie; Wang, Mengting; Zhen, Cong’ai; Huang, Xinzheng (Frontiers in Physiology, 2024)
Plumbagin is an important phytochemical and has been reported to exhibit potent larvicidal activity against several insect pests, However, the insecticidal mechanism of plumbagin against pests is still poorly understood. This study aimed to investigate the insecticidal activities of plumbagin and the underlying molecular mechanisms against a devastating agricultural pest, the fall armyworm Spodoptera frugiperda.The effects of plumbagin on S. frugiperda larval development and the activities of two detoxification enzymes were initially examined. Next, transcriptomic changes in S. frugiperda after plumbagin treatment were investigated. Furthermore, RNA-seq results were validated by qPCR.Results: Plumbagin exhibited a high larvicidal activity against the second and third instar larvae of Spodoptera frugiperda with 72 h LC50 of 0.573 and 2.676 mg/g, respectively. The activities of the two detoxification enzymes carboxylesterase and P450 significantly increased after 1.5 mg/g plumbagin treatment. Furthermore, RNAseq analysis provided a comprehensive overview of complex transcriptomic changes in Spodoptera frugiperda larvae in response to 1.5 mg/g plumbagin exposure, and revealed that plumbagin treatment led to aberrant expression of a large number of genes related to nutrient and energy metabolism, humoral immune response, insect cuticle protein, chitin-binding proteins, chitin synthesis and degradation, insect hormone, and xenobiotic detoxification. The transcriptomics data was further validated by qPCR.Discussion: Our findings provide a valuable insight into understanding the insecticidal mechanism of the phytochemical plumbagin.